Kajian Unsur Hara Mikro Tanah Untuk Peningkatan Produksi Pangan pada Lahan Sawah di Kecamatan Penebel, Tabanan - A.A. NYOMAN SUPADMA; I MADE ADNYANA; I NYOMAN PUJA (Agrotrop : Journal on Agriculture Science, 2013)
Assessment of Micro Nutrient of Soil for Improving Food Production on Paddy Field in The District of Penebel, Tabanan Research of soil micro nutrient was carried out on paddy soil in district Penebel, Tabanan regency, starting July until October 2013, which was conducted by soil survey and laboratory analysis. The experiment consists of several stages such as the formation of the land unit based on the compilation maps of soil type, geology and slope, obtained 11 land units. Each unit taken some samples depending on the area, location and slope, so have got 50 soil samples. Soil samples were taken at a depth of 0-20 cm. Further, the content of micro nutrients Zn, Cu, Fe, Mn analyzed with EDTA extraction at Soil laboratory, Faculty of Agriculture, Udayana University. In addition it also analyzed of the soil macro nutrients content: total-N, available- P, available-K, C- organic matter, soil pH and salinity. Soil analysis showed that the micro nutrient content of Fe ranged from 59.672 to 66.382 ppm (classified as moderate), Mn ranged from 11.960 to 33.786 ppm (relatively low), Cu ranged from 5.426 to 23.204 ppm (very low to low), and Zn ranged from 1.818 to 9.058 ppm (very low to moderate). The paddy soil in the district Penebel, containing moderate of micronutrients Fe content and Mn contain relatively low; Cu content are very low to low; and Zn content are mostly very low to low. While the content of macro nutrient elements such as N and P are low to moderate, but the content of K is very high. C-organic content classified as moderate to high, and soil acidity is slightly acid soil. The limiting factors of rice production were Zn, Cu and Mn. Fertilization of micro nutrients needs to increase rice production in the district Penebel. To obtain suitable micro-nutrient fertilizer dosage to increase rice yield in district Penebel, it is needs to be done research of micro nutrients testing especially Zn, Cu, and Mn.